Investigation of Sociocultural Factors in Affecting English Speaking Ability of English Major Students at Lakidende University - Wahyudi, Iin (Indonesian Research Journal on Education, 2025)
English speaking ability is still difficult to master for some people, including English major students who academically should be able to speak English fluently and correctly. This can be influenced by several factors, and based on information from the research subjects, shame and fear of making mistakes are some of the things that make them afraid to speak English. These problems are part of sociocultural factors. Therefore, this research aims to find out more about what sociocultural factors can affect students’ speaking ability. This research uses a qualitative method, a case study type. In addition, the subjects and this research were 5th semester students at Lakidende University, totaling 11 students. Then, the data in this research were analyzed through three stages, namely data reduction, data display and drawing conclusions. Then the results of this research indicate that sociocultural factors that can affect students’ English speaking ability consist of the role of parents, classroom environment, English learning community and the views or attitudes of people in the environment around the students. The conclusion of this research is that it can be concluded that the sociocultural factors that most affect English speaking ability include the role of students’ parents and a supportive classroom environment. While the next factor that also has a large affect in affecting students’ English speaking ability is the existence of an English learning community. As for sociocultural factors that do not have a broad and significant affect, namely the attitudes or views given by people in the environment around the students.